Anticipated stigma and quality of life among people living with chronic illnesses. - Earnshaw, Valerie A; Quinn, Diane M; Park, Crystal L (Chronic illness, 2011)
OBJECTIVES: We examined the process by which anticipated stigma relates to quality of life among people living with chronic illnesses. We hypothesized that stress, social support and patient satisfaction mediate the relationships between three sources of anticipated stigma and quality of life. METHODS: Data were collected from adults living with chronic illnesses recruited from support groups and online communities, and were analysed with path analysis. RESULTS: RESULTs demonstrated that stress mediated the relationships between anticipated stigma from friends and family, and work colleagues with quality of life; social support mediated the relationships between anticipated stigma from friends and family, and work colleagues with quality of life; and patient satisfaction mediated the relationship between anticipated stigma from healthcare providers with quality of life. The final path model fit the data well (χ (2) (8) = 8.66, p = 0.37; RMSEA = 0.02; CFI = 0.99; SRMR = 0.03), and accounted for 60% of the variance in participants' quality of life. DISCUSSION: This work highlights potential points of intervention to improve quality of life. It calls attention to the importance of differentiating between sources of anticipated stigma in clinical settings, interventions and research involving people living with chronic illnesses.